2007
DOI: 10.1007/s11064-006-9244-2
|View full text |Cite
|
Sign up to set email alerts
|

Tyrosine Nitration is a Novel Post-translational Modification Occurring on the Neural Intermediate Filament Protein Peripherin

Abstract: The biological implication of protein tyrosine nitration in signaling pathways triggered by nitric oxide is recently emerging. Here we report for the first time that nitrotyrosination occurs in the neural intermediate filament protein peripherin. In neuron-like PC12 cells, nitrated peripherin is associated with the cytoskeleton fraction, its level increases during the progression of NGF-induced differentiation and the nitrated protein remains closely associated with stable microtubules. Tyr 17 and Tyr 376 were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…From this point of view it is very interesting to note that we found in the same peptide nitrated Tyr 197 and one (in brain) or two (in PC12 cells) residues phosphorylated at Ser or Thr suggesting that nitration does not prevent tau protein to be phosphorylated in keeping with our previous observations on peripherin [26] and with the data reported by Monteiro [38] and Di Stasi et al [39] who proposed a possible cooperation in signaling processes between nitration and phosphorylation. On the other hand, Tyr 197 is predicted to be a phosphorylation site for tyrosine kinases consistent with the data reported by Sacksteder et al [13] who found that nitration in the brain involves many tyrosine residues that are predicted to be phosphorylated.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…From this point of view it is very interesting to note that we found in the same peptide nitrated Tyr 197 and one (in brain) or two (in PC12 cells) residues phosphorylated at Ser or Thr suggesting that nitration does not prevent tau protein to be phosphorylated in keeping with our previous observations on peripherin [26] and with the data reported by Monteiro [38] and Di Stasi et al [39] who proposed a possible cooperation in signaling processes between nitration and phosphorylation. On the other hand, Tyr 197 is predicted to be a phosphorylation site for tyrosine kinases consistent with the data reported by Sacksteder et al [13] who found that nitration in the brain involves many tyrosine residues that are predicted to be phosphorylated.…”
Section: Discussionsupporting
confidence: 90%
“…Nitrated peaks were identified by an increase in mass of 45 (NO 2 ), 29 (NO), 13 (N) and 15 (NH 2 ) units [29][30]. To further confirm the nitration, nitrotyrosine was converted to aminotyrosine by reduction with Na 2 S 2 O 4 resulting in a single mass shift corresponding to amination of tyrosine [29,26]. In details, after in gel tryptic digestion and peptides extraction, the peptide mixture was split in two aliquots.…”
Section: Western Blot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…NO triggers a switch to growth arrest and neuronal differentiation [29] and it modulates neuritogenesis by regulating signaling pathways through several mechanisms [52] such as binding to heme or iron sulphur sites in regulatory proteins [53] or by modifying tyrosines in cytoskeletal proteins [37,54-56]. Unlike most other endogenous messengers that are deposited in vesicles, NO cannot be stored inside the cells, rather its signaling capacity must be controlled at the level of biosynthesis and local availability [57].…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that some of the major cytoskeletal proteins, including actin and tubulin, are nitrated in PC12 cells (Tedeschi et al, 2005) and in vivo in rat and mouse brain (Tedeschi et al, 2007; Nonnis et al 2008) under physiological conditions.…”
Section: Resultsmentioning
confidence: 99%